Bone invasion of squamous cell carcinoma of the oral cavity, clinical-pathological analysis of 62 cases - Vaz Vanini, Jaqueline (2020)
Prognosis for patients with squamous cell carcinoma (SCC) in oral cavity with bone invasion presence is concerning. Bone invasion patterns can be used to indicate aggressiveness and can be correlated with tumor clinical behavior. Objective: To evaluate bone invasion histopathological patterns in patients with oral cavity SCC and correlate them with the survival rate. Materials and methods: 62 patients with presence of SCC in the oral cavity as well as bone invasion were recruited for this study. Epidemiological and histopathological characteristics were tabulated and analyzed. Fischer's Square and Exact Tests were used to verify any statistical associations between the data. Results: More men were affected, especially in the fifth decade of life, and a strong association with smoking and chronic alcoholism was observed. Deaths were reported in 58% of patients, over a period of 5 years. The most prevalent histological pattern was the infiltrative, associated with lower survival rates. Conclusion: An analysis of the histopathological patterns of oral cavity SCC can be used as a prognostic factor thereby assisting with the decision of which oncological treatment approach to use.